THE ROLE OF TAX POTENTIAL IN IMPROVING THE QUALITY OF THE FISCAL SYSTEM - Ermekbayeva Bayan Zhundibayevna; Alimov Nurlybi Daletkazyuly (Academic Journal of Physical and Chemical Sciences, 2020)
The term “tax potential” is studied in the article. In the introductory part of the article, the authors compared the meaning of two concepts, such as the tax and budget potential of the region, and showed the difference between the two concepts. The definitions of different authors of the tax potential as an economic category are given. The main section analyzes the dynamics of tax revenues to the republican and local budgets of the city of Almaty for 2016-2018. The factors affecting the tax potential of the region, including the influence of the shadow economy on the state budget, are identified. The concluding section presents specific ways to increase tax potential.